Applying Faceted Classification to the Personal Organization of Electronic Records: Insights into the User Experience - Mas, Sabine; Maurel, Dominique; Alberts, Inge (Archivaria, 2011)
Despite recent technological advances, most operating systems still support the organization of electronic records according to hierarchical structures or directory trees. Although seemingly intuitive, these organization methods can be limiting as records are classified in one place according to one person’s logic, thereby making it difficult for other users to relate. Furthermore, the inherent boundaries of such a structure necessitate making arbitrary decisions on the specific criteria upon which the classification will be based (e.g., the administrative function or activity, the document type, or its subject) even though a document may have several attributes and require classification in several classes. In this article, an original faceted approach to support electronic records organization is proposed in order to eliminate some of these well-known constraints. Insights into the user experience are now needed to improve the theoretical models and enhance the proposed faceted navigation interface. To that end, this paper discusses a pilot study investigating the pertinence of augmenting traditional hierarchical classification schemes with a faceted classification for records organization in a decentralized, digital environment. RÉSUMÉ Malgré les progrès technologiques récents, la plupart des systèmes d’exploitation continuent de classer les documents numériques selon une structure hiérarchique ou arborescente. Bien qu’elles puissent avoir l’air intuitives, ces méthodes de classement peuvent être limitantes puisque les documents sont classés dans un endroit donné selon la logique d’un seul individu, ce qui rend la compréhension difficile pour les autres personnes. De plus, les frontières inhérentes à ce type de structure exigent que les gens prennent des décisions arbitraires à partir des critères spécifiques sur lesquels le classement sera effectué (par exemple : la fonction ou l’activité administrative, le type de document, ou son sujet), même si un document peut avoir plusieurs attributs et pourrait être classé à divers endroits. Dans ce texte, les auteurs proposent une approche originale à facettes pour l’organisation des documents numériques, dans le but d’éliminer certaines de ces contraintes bien connues. Un aperçu de l’expérience des utilisateurs s’avère maintenant nécessaire afin d’améliorer à la fois les modèles théoriques et l’interface de navigation à facettes proposé. À cette fin, les auteurs présentent une étude pilote visant à examiner la pertinence d’ajouter aux schémas de classification traditionnels une classification à facettes pour le classement des documents dans un environnement numérique décentralisé.